Análise da relação entre depressão materna e índices de risco ao desenvolvimento infantil - Carlesso, Janaína Pereira Pretto (2011)
This study examined the possible relationship between maternal depressive states and changes in levels of risk to child development, in a sample of mothers of babies born in medium-sized city and around the central region of Rio Grande do Sul (RS). The survey was conducted in University Hospital in which the children were newborn hearing screening in the period from March to May 2010, with the mother-infant dyads. In the data collection was used a structured interview on socioeconomic, demographic, obstetric and psychosocial and experience of motherhood. To investigate the maternal depressed mood was used Beck Depression Inventory (BDI). In the evaluation of the babies was done filming the interaction of mother-infant dyad and implementation of Clinical Indicators of Risk for child development (IRDIs).Most mothers in this study was not suffering from depression, and low socioeconomic status and non - planned birth were the most common risk factors for the onset of depression in the postpartum period. The analysis showed that a higher proportion of babies with IRDIs altered when levels of maternal depression are elevated in the postpartum period and may adversely affect the interaction of mother-infant and mainly reflected as a risk factor for child development. The presence of social support, especially fellow and no difficulties in forming the maternal experience are variables significantly associated with absence of risk for child development. Therefore, not only the presence or absence of depression, but factors such family support and maternal role constitution are the most important factors for the full development of the baby. This paper suggests the need for an interface between psychology, speech pathology and other health professionals in monitoring the postpartum period in order to minimize the consequences of postpartum depression and help the mother-baby when the parental role are not going so good enough.